2005
DOI: 10.1093/abbs/37.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Papillomavirus Type 16 L1 Protein in Transgenic Tobacco Plants

Abstract: To develop a plant expression system for the production of the human papillomavirus type 16 (HPV16) vaccine, we investigated whether the HPV16 L1 protein can be expressed in tobacco plants and whether it can be used as the cheapest form of edible vaccine. The HPV16 L1 coding sequence was amplified by PCR using specific primers from the plasmid pGEM-T-HPV16 containing the template sequence, and subcloned into the intermediate vector pUCmT and binary vector pBI121 consecutively to obtain the plant expression pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 9 publications
0
18
1
1
Order By: Relevance
“…The promising results generated in preclinical animal studies have led to phase I/II clinical trials using the HPV-16 VLP vaccine delivered intramuscularly. Recently, Liu et al49 showed that the HPV-16 L1 protein could be expressed in transgenic tobacco plants and that the expressed protein possessed the natural features of the HPV-16 L1 protein, implying that the HPV-16 L1 transgenic plants could potentially be used as an edible vaccine. These studies suggest the possibility of vaccinating large populations with the HPV VLPs without using syringes.…”
Section: Current Hpv Vaccinesmentioning
confidence: 99%
“…The promising results generated in preclinical animal studies have led to phase I/II clinical trials using the HPV-16 VLP vaccine delivered intramuscularly. Recently, Liu et al49 showed that the HPV-16 L1 protein could be expressed in transgenic tobacco plants and that the expressed protein possessed the natural features of the HPV-16 L1 protein, implying that the HPV-16 L1 transgenic plants could potentially be used as an edible vaccine. These studies suggest the possibility of vaccinating large populations with the HPV VLPs without using syringes.…”
Section: Current Hpv Vaccinesmentioning
confidence: 99%
“…Plants have been used as ''green bioreactors'' for the production of essential enzymes (Hong et al 2004;Chiang et al 2005) and other proteins (Liu et al 2005), carbohydrates (Sahrawy et al 2004) and lipids (Qi et al 2004) while requiring minimal inputs of raw materials and energy (Teymouri et al 2004). Production of biomolecules in plants, considered as molecular farming, is one approach to improve the economics and increase the lowcost production efficiency of these biomolecules (Fischer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that transgenic plants that express antigens could be used for low-cost vaccine production systems, and a number of human viral antigens have now successfully been expressed in transgenic plants (Arntzen et al 1994;Mason and Arntzen 1995;McGarvey et al 1995;Richter et al 2000;Huang et al 2005;Liu et al 2005;Varsani et al 2006).…”
Section: Discussionmentioning
confidence: 99%